KRAS mutation status is associated with specific pattern of genes expression in pancreatic adenocarcinoma. (July 2015) - Bittoni, Alessandro; Piva, Francesco; Santoni, Matteo; Andrikou, Kalliopi; Conti, Alessandro; Loretelli, Cristian; Mandolesi, Alessandra; Lanese, Andrea; Pellei, Chiara; Scarpelli, Marina; Principato, Giovanni; Cascinu, Stefano
ABSTRACT : Aims: To evaluate potential differences at a molecular level between KRAS mutant tumors (MT) and KRAS wild-type (WT) pancreatic tumors and the biological and prognostic significance of different KRAS mutations.Materials & methods: Expression of a panel of 29 genes was analyzed in KRAS WT and MT tumors. Effects of KRAS mutation and gene expression levels were assessed on patients' survival.Results: MUC6 (p = 0.009), HGF (p = 0.011), VEGFR-2 (p = 0.020) and VEGFB (p = 0.026) were significantly more expressed and SMAD4 was less suppressed (p = 0.003) in WT KRAS . Contrariwise, SHH (p = 0.012) and IHH (p = 0.031) were more expressed in MT KRAS patients. No OS difference was found between WT and MT KRAS tumors.Conclusion: KRAS mutation status seems to identify two different subtypes of pancreatic ductal adenocarcinoma with similar outcome but distinct molecular features and probably different therapeutic targets.